2022
DOI: 10.2196/38663
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Electronic Visits for Smoking Cessation and Chronic Obstructive Pulmonary Disease Screening in Primary Care: Randomized Controlled Trial of Feasibility, Acceptability, and Efficacy

Abstract: Background Most smokers with chronic obstructive pulmonary disease (COPD) have not yet been diagnosed, a statistic that has remained unchanged for over two decades. A dual-focused telehealth intervention that promotes smoking cessation, while also facilitating COPD screening, could help address national priorities to improve the diagnosis, prevention, treatment, and management of COPD. The purpose of this study was to preliminarily evaluate an integrated asynchronous smoking cessation and COPD scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Additionally, all cessation outcomes were based on self-report. In our team's prior remote trials, biochemically verified abstinence rates have been somewhat lower than self-reported abstinence [53]. Finally, study generalizability may be limited only to those fluent in English who own a smartphone, and the durability of intervention effects beyond 12 weeks is unclear.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, all cessation outcomes were based on self-report. In our team's prior remote trials, biochemically verified abstinence rates have been somewhat lower than self-reported abstinence [53]. Finally, study generalizability may be limited only to those fluent in English who own a smartphone, and the durability of intervention effects beyond 12 weeks is unclear.…”
Section: Discussionmentioning
confidence: 95%
“…Fortunately, there has been a study of online diagnosis and visits, and encouraging results have been achieved. It showed that participants were more inclined to complete online follow-ups [ 22 ]. In the future, online diagnosis and treatments might be achieved in several advanced regions in China, expecting to acquire positive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, health education is necessary and urgent. Fortunately, there has been a study of online diagnosis and visits, and positive results have been achieved [15]. In the future, online diagnosis and treatments might be conducted in several advanced regions in China, expecting to acquire positive responses.…”
Section: Discussionmentioning
confidence: 99%